Prenatal reflex DNA screening for trisomies 21, 18, and 13. (August 2018) - Wald, Nicholas; Huttly, Wayne; Bestwick, Jonathan; Old, Robert; Morris, Joan; Cheng, Ray; Aquilina, Joe; Peregrine, Elisabeth; Roberts, Devender; Alfirevic, Zarko
Abstract Purpose The purpose of the study was to determine the screening performance of prenatal reflex DNA screening for trisomies 21 (T21), 18 (T18), and 13 (T13) as part of a routine service at five hospitals. Methods Women who accepted screening had a first-trimester combined test (pregnancy-associated plasma protein A, free β-human chorionic gonadotropin, nuchal translucency interpreted with maternal age). Those with a risk of having an affected pregnancy ≥1 in 800 were reflexed to a DNA sequencing test using stored plasma from the original blood sample, thereby avoiding the need to recall them. Results Of 22, 812 women screened (including 106 with affected pregnancies), 2, 480 (10.9%) were reflexed to DNA testing; 101/106 were detected (69/73 T21, 24/25 T18, and 8/8 T13), a 95% detection rate (95% confidence interval 89–98%) with four false positives (0.02%, 95% confidence interval 0.00–0.05%). The odds of being affected given a positive result were 25:1. Of the 105 screen-positive pregnancies, 91 (87%) had an invasive diagnostic test. Reflex DNA screening avoided up to 530 invasive diagnostic tests compared with using the combined test. Conclusion Reflex DNA screening was successfully implemented in routine care, achieving a high detection rate, low false-positive rate, and, consequently, greater safety with fewer invasive diagnostic tests than other methods of screening.